P14.01 Incidence and impact of venous thromboembolism and major bleeding in patients with glioblastoma. (9th September 2021) - Kaptein, F H J; Stals, M A M; Klaase, E; Kapteijn, M Y; Cannegieter, S C; Taphoorn, M J B; Dirven, L; Huisman, M V; Koekkoek, J A F; Klok, F A
Abstract: BACKGROUND: Patients with glioblastoma are considered to be at high risk of venous thromboembolism (VTE) and major bleeding (MB), although reliable incidence estimates are lacking. The aim of this study was to assess the cumulative incidence, risk factors and prognostic impact of VTE and MB in a large cohort of glioblastoma patients. MATERIAL AND METHODS: Patients diagnosed with glioblastoma between 2004–2020 from the Leiden University Medical Center and Haaglanden Medical Center were included and followed from 6 months before date of histopathological glioblastoma diagnosis up to two years after, or until an outcome of interest (VTE and MB) or death occurred. Cumulative incidences were estimated using Kaplan-Meier and cumulative incidence competing risk methods. Outcome predictors were determined with multivariable (time-dependent) Cox models. RESULTS: Of the 967 included patients, 631 died, 101 were diagnosed with VTE and 130 with MB during a median follow-up of 15 months (IQR 9–22). The majority of MBs were intracranially (94%), of which half was within 4 weeks post-surgery (51%). Ambulant patients did not routinely receive pharmacological thromboprophylaxis. The adjusted 2.5-year-cumulative incidence of VTE was 12% (95%CI 10–14) and of MB 16% (95%CI 13–18). One year increase in age (HR 1.03, 95%CI 1.01–1.05), tumor resection (vs. biopsy: HR 0.56, 95%CI 0.35–0.89) and performance status (ECOG >1 vs ≤1: HR 1.8, 95%CI 1.2–2.7) were independent predictors of VTE (a biopsy rather than resection was performed in patients with the worst prognosis). MB and VTE predicted all-cause mortality (adjusted HR 1.7, 95%CI 1.3–2.1 and 1.3, 95%CI 0.99–1.6 respectively). CONCLUSION: The incidences of VTE and MB in patients with glioblastoma are high, with both complications associated with a poor prognosis. Our observations emphasize the need for prospective studies to determine optimal thromboprophylaxis and VTE treatment strategy in these patients.